ENGLISH BORROWING TRANSLATION FROM ENGLISH INTO INDONESIAN SUBTITLE IN THE REDEEMING LOVE FILM - Bertaria Sohnata Hutauruk (Journal of English Language and Culture, 2022)
Borrowing is one the various techniques to utilize the word to keeping the source language’s original words and phrases or sentence in the target language’s version. The researcher focus to find the types borrowing and dominant of borrowing in the especially in learning English. The researcher used Molina and Albir theories about borrowing  the divided into two types there is pure borrowing and naturalized borrowing. The data sheets used as secondary instruments that during time there is collecting, classifying, analyzing, discussing and result the data This study was conducted using  a qualitative method. The aim of the resaarch found many borrowing words in two types borrowing pure and naturalized borrowing in the film. And from the result that the dominant types is naturalized borrowing in 61 data, 36 or  59,16% is naturalized and 25 or 40,99% the pure borrowing. Based on the dominant types borrowing founded in the redeeming love film.